Causes of chronic productive cough: An approach to management. Issue 9 (September 2015) - Martin, Matthew J.; Harrison, Tim W.
Abstract A chronic 'productive' or 'wet' cough is a common presenting complaint for patients attending the adult respiratory clinic. Most reviews and guidelines suggest that the causes of a productive cough are the same as those of a non-productive cough and as such the same diagnostic pathway should be followed. We suggest a different diagnostic approach for patients with a productive cough, focussing on the conditions that are the most likely causes of this problem. This review is intended to briefly summarise the epidemiology, clinical features, pathophysiology and treatment of a number of conditions which are often associated with chronic productive cough to aid decision making when encountering a patient with this often distressing symptom. The conditions discussed include bronchiectasis, chronic bronchitis, asthma, eosinophilic bronchitis and immunodeficiency. We also propose an adult version of the paediatric diagnosis of protracted bacterial bronchitis (PBB) in patients with idiopathic chronic productive cough who appear to respond well to low dose macrolide therapy.